2022
DOI: 10.3390/atmos13020211
|View full text |Cite
|
Sign up to set email alerts
|

Interannual and Seasonal Variation of Optical and Microphysical Properties of Aerosol in the Baikal Region

Abstract: The paper analyzes the interannual, seasonal variations of the optical and microphysical characteristics of aerosol in the Baikal region atmosphere according to measurements using the CIMEL sun photometer of the AERONET network at Tory station and according to the data of expedition measurements using the SP-9 sun photometer on the southeastern coast of Lake Baikal from 2010 to 2020. It is shown that in recent years, there has been an increase of the average monthly aerosol optical depth (AOD) values in the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Increased concentrations of fine dispersed aerosols in the warm period are due to additional emission of organic aerosol during the flowering period of plants, soil aerosol, the influence of smoke aerosol from wildfires and peat fires, etc. [11].…”
Section: Resultsmentioning
confidence: 99%
“…Increased concentrations of fine dispersed aerosols in the warm period are due to additional emission of organic aerosol during the flowering period of plants, soil aerosol, the influence of smoke aerosol from wildfires and peat fires, etc. [11].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 1c shows a decrease in the singlescattering albedo with wavelength, which is typical for the predominance of absorbing aerosols in the atmosphere, such as black carbon. In the long-term change in the finely dispersed component of AOD, a growth trend and high variations due to smoke from wildfires were noted [7]. To identify the main features of the spatiotemporal variability of aerosol characteristics in the atmosphere of the Baikal region, the average spectral characteristics of the aerosol optical depth of the atmosphere for the "smoke/clear atmosphere" conditions are considered.…”
Section: Resultsmentioning
confidence: 99%
“…Natural, largescale events of aerosol intrusions have been researched by Sun et al (2022), who studied two extreme dust events over North China in March, 2021, by using AERONET in situ observations and CALIPSO satellite data to obtain the distribution characteristics of dust aerosol optical properties along their transport pathways [11]. Additionally, Dementeva et al (2022) analyzed AERONET data collected over a 10-year period, and found that there was a significant increase in smoke aerosols during the summer months, which was caused by large-scale wildfires in the boreal forests surrounding Lake Baikal [12]. In Southeastern Europe, long-term aerosol trends have been researched using AERONET datasets.…”
Section: Introductionmentioning
confidence: 99%